Recent developments in user-job management with Ganga. Issue 6 (December 2015) - Currie, R; Elmsheuser, J; Fay, R; Owen, P H; Richards, A; Slater, M; Sutcliffe, W; Williams, M
Abstract: The Ganga project was originally developed for use by LHC experiments and has been used extensively throughout Run1 in both LHCb and ATLAS. This document describes some the most recent developments within the Ganga project. There have been improvements in the handling of large scale computational tasks in the form of a new GangaTasks infrastructure. Improvements in file handling through using a new IGangaFile interface makes handling files largely transparent to the end user. In addition to this the performance and usability of Ganga have both been addressed through the development of a new queues system allows for parallel processing of job related tasks.